(untitled) (Journal of the College of Languages (JCL), 2021)
The present paper sheds light on irony as one of the most important and most common linguistic phenomena in modern linguistics, in general ,and in discourse in particular, whether it is (political, literary, journalistic, etc.). When irony is used correctly or positively, it paves the way for the speaker to gain the approval of other parties participating in the dialogue and dissolve barriers between them. It is a simple multi-functional linguistic style and an expression of one’s meaning by using language that normally signifies the opposite according to the context and the situation. Therefore, it is necessary to study its characteristics, define its functions and traces the extent of its influence on the recipient, especially in political discourse, for the important role it plays in determining the state’s strategies in many issues, and the different linguistic characteristics and styles hidden goals, motives and purposes. The study provides speeches examples for some political figures that employ irony in their speeches. The conclusion sums up the findings of the study. Аннотация. Ирония-основной элемент нашей статье. Она является составной частью современной лингвистики в общем и в современного дискурса в частности независимо от его вида (политического, художественного, публицистического и т.д.), по этой причине изучение особенностей ее употребления в языке служит адекватному пониманию высказывания и в конечном счете, к продуктивному процессу общения. И, в частности, облегчения ее понимания в анализе политического дискурса. Структура статье включает определение иронии, ее общие классификаций, практические примеры и заключение выражающее наше видение в работе над проблемой. Это и есть часть нашей магистерской работе об анализе политического дискурса.